A study on effects of social media influencers on university students purchasing decision - Tai, Yuen Zheng (2023)
The study aims to study the relation between social media influencers and the effects of influential marketing. The study strives to find out how purchasing decision of the target group is affected by the social media influencers. Furthermore, what is the factors that university students view as the credibility of social media influencers they followed. The main group of research will be on university students across Malaysia, who mainly aged between 18 to 24. This age group is the large audiences for social media influencers. The study believes in a hypothesis that the higher followers a social media influencer has, the perceived credibility on that influencer in higher. With this hypothesis, researchers believe that an influencer with higher followers will bring more impact to the university students’ purchasing decision. The methodology adopted in this research is quantitative research through online survey on Microsoft form. Total of 100 university students in Malaysia will be surveyed on questions mentioned below. The data will be analyzed with Statistical Package for Social Science (SPSS) to determine how social media influencers’ effect on university students’ purchasing decision.